Lessons learned from the world's first CBDC - Aleksi Grym (Bank of Finland, 2020)
Central banks worldwide are currently exploring so called Central Bank Digital Currencies (CBDC). The Avant smart card system created by the Bank of Finland in the 1990's can be considered the world's first CBDC and the only one so far that has gone into production. Avant cards were based on smart card technology similar to that used in debit and credit cards today. Even though the system was initiated, developed, and for the first few years operated by the central bank, it was eventually spun off and sold to commercial banks. Once debit cards became less expensive and were upgraded to use smart card technology, Avant became obsolete and was shut down. The story of Avant can give us valuable insight contributing to the ongoing discussion regarding CBDC.
urn:nbn:fi:bof-202009152340
Keywords: 330; CBDC; e-money